2011
DOI: 10.1039/c1cc14586j
|View full text |Cite
|
Sign up to set email alerts
|

Increased open circuit voltage in fluorinated benzothiadiazole-based alternating conjugated polymers

Abstract: Small band-gap conjugated polymers based on monofluoro- and difluoro-substituted benzothiadiazole were developed. Highly efficient polymer solar cells (PCE as high as 5.40%) could be achieved for devices made from these polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
195
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 244 publications
(212 citation statements)
references
References 21 publications
12
195
1
2
Order By: Relevance
“…Indeed, conventional polycondensation methods do not allow regioselectivity control when using asymmetric monomers [17]. Therefore, the lack of control of the monomer orientation along the conjugated backbone leads to regiorandom polymers [40][41][42][43][44] that are known to suffer from lower structural organization in solid state and consequently possess, most often, inferior charge transport properties [45]. An alternative stepwise chemical approach consists in synthesizing symmetric monomers from unsymmetrical fragments, thanks to their regiochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, conventional polycondensation methods do not allow regioselectivity control when using asymmetric monomers [17]. Therefore, the lack of control of the monomer orientation along the conjugated backbone leads to regiorandom polymers [40][41][42][43][44] that are known to suffer from lower structural organization in solid state and consequently possess, most often, inferior charge transport properties [45]. An alternative stepwise chemical approach consists in synthesizing symmetric monomers from unsymmetrical fragments, thanks to their regiochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we found that the l of K 8 Al 8 Si 38 is much superior to those of, e.g., a-Si: 1 cm 2 V À1 s À1 for electrons and 0.01 cm 2 V À1 s À1 for holes [41][42][43][44] and to those of organic materials: $0.008 cm 2 V À1 s À1 for electrons and $0.002 for holes. 45 In addition, the ratio l e =l h is $5 in K 8 Al 8 Si 38 , while it can be as high as 100 in a-Si (it is $3 in c-Si).…”
Section: A Clathratesmentioning
confidence: 99%
“…A comprehensive survey of the chemical methods for designing high PCE polymers found that the inductive effect such as introducing fluorine or sulfur atoms to the polymer backbone has been considered as one of the most effective and successful methods, which can bring about simultaneous improvement of V oc , J sc , and FF on their OSCs devices. 26−30 However, chemically introducing fluorine 31 or sulfur 32 always makes the synthetic route more complicated and expensive, and fluorine atoms sometimes reduce the solubility of the polymers remarkably. shown in Scheme 1, analogous hexyl and cyclohexyl were chosen as side chains because they have the same carbon number and similar electronic effect except they were connected to the polymer backbone with a primary carbon and a secondary carbon, respectively.…”
Section: −5mentioning
confidence: 99%